(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cetyl trimethyl ammonium bromide stabilized perylene nanoparticles (CTAB-PNs) 20 to 31 nm in diameter were prepared by modified reprecipitation method in aqueous solution under ultrasonic treatment. A spectrofluorimetric method for the quantitative determination of ATP based on the fluorescence quenching of CTAB-PNs by ATP in aqueous solution was proposed. Under the most favourable conditions, the fluorescence intensity of PNs monitored at excitation wavelength λex = 380 nm was quenched by gradual addition of concentration of ATP. The fluorescence quenching results found to fit into Stern-Volmer relation in the range of 0.5 to 15 μM with a correlation coefficient of 0.9970. The limit of detection was 3.92 μM. The method based on fluorescence quenching was successfully applied for quantitative determination of ATP.